Solid plane material with excellent hot water resistance and preparation method thereof

By using a specific ratio of polyacrylate resin, aluminum hydroxide, coupling agent, and crosslinking agent in the acrylic solid surface material, a stable crosslinked network structure is formed, which solves the problem of pigment precipitation under hot water impact and improves the hot water resistance and stability of the material.

CN119264591APending Publication Date: 2025-01-07ZHUHAI SHENGXIYUAN MECHANICAL & ELECTRICAL EQUIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411610894.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing acrylic solid surface materials are prone to pigment leaching under the impact of hot water, resulting in a lighter color, which affects the service life and application range.

Method used

By combining polyacrylate resin, aluminum hydroxide, coupling agent and crosslinking agent in a specific ratio, a stable crosslinked network structure is formed, which enhances the interfacial bonding force and the heat resistance of the material, and prevents pigment precipitation.

Benefits of technology

It significantly improves the hot water resistance and stability of solid surface materials, prevents pigments from leaching out in hot water environments, and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005130872100000051
    Figure BDA0005130872100000051
Patent Text Reader

Abstract

The invention relates to a solid plane material with excellent hot water resistance and a preparation method thereof, and relates to the field of building materials. The solid surface material comprises the following components in parts by weight: 32-40 parts of polyacrylate resin; 54 to 68 parts of aluminum hydroxide; 0.3 to 5.0 parts of a coupling agent; 0.1 to 4 parts of a cross-linking agent; 0.2 to 3.0 parts of a curing agent; and 0.3-6 parts of a pigment. Through the synergistic effect of the coupling agent and the cross-linking agent, the stability of the solid surface material is remarkably improved, the formation of a cross-linked network is consolidated, the pigment is prevented from being separated out by hot water, and the stability and durability of the surface material in long-term use are ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of building materials, and more specifically, to a solid surface material with excellent hot water resistance and a preparation method thereof. Background Art

[0002] Acrylic solid surface materials are mainly prepared by mixing and curing acrylic resin (acrylates), aluminum hydroxide powder, curing agent, cross-linking agent and pigment. This solid surface material has diverse functions and rich colors, and is widely used in countertops such as kitchen counters, baths, dressing tables, wash basins and other construction fields. However, due to the poor compatibility and loose combination of organic (acrylates) and inorganic components (aluminum hydroxide), in some areas such as bathtubs, during long-term use, the repeated impact of hot water causes the pigment to precipitate from the inside of the solid surface material, which eventually causes the color to become lighter, especially when the color is darker, which limits the application of this type of solid surface material. Summary of the invention

[0003] The primary purpose of the present invention is to solve the problem that the above-mentioned solid surface material is not resistant to hot water and the pigment is easily analyzed from the inside of the solid surface material under repeated impact of hot water, and to provide a solid surface material with excellent hot water resistance.

[0004] A further object of the present invention is to provide a method for preparing the above-mentioned solid surface material with excellent hot water resistance.

[0005] The above-mentioned object of the present invention is achieved by the following technical solutions:

[0006] A solid surface material with excellent hot water resistance comprises the following components in parts by weight: 32-40 parts of polyacrylate resin; 54-68 parts of aluminum hydroxide; 0.3-5.0 parts of coupling agent; 0.1-4 parts of cross-linking agent; 0.2-3.0 parts of curing agent; and 0.3-6 parts of pigment.

[0007] The present invention creatively solves the problem that the solid surface material is not resistant to hot water and the pigment is easily precipitated under repeated impact of hot water through a specific component ratio, especially the synergistic effect of a coupling agent and a cross-linking agent. Specifically, the polyacrylate resin in the formula is used as a matrix material, providing good processing performance and a certain heat resistance basis. At the same time, aluminum hydroxide, as an inorganic filler, significantly enhances the mechanical strength and heat resistance of the surface material. However, to achieve a close combination between these inorganic fillers and the resin matrix and prevent thermal stress concentration and performance degradation caused by interface defects, a coupling agent is required to play a key role. As a special surfactant, one end of the coupling agent molecule can react with the polar group in the resin matrix, and the other end can react with the hydroxyl group on the surface of the inorganic filler such as aluminum hydroxide, thereby establishing a strong chemical bond between the resin and the inorganic filler, effectively improving the interface bonding force, and enhancing the compactness and durability of the overall structure. On this basis, the addition of the cross-linking agent, by reacting with the active groups in the resin molecules, forms a stable cross-linked network structure, further improving the internal structural strength and heat-resistant deformation temperature of the surface material. The role of the cross-linking agent is not only to enhance the mechanical properties of the material, but more importantly, it limits the movement of the resin molecular chain at high temperature by forming a three-dimensional network structure, thereby improving the thermal stability of the material. This synergistic effect of the coupling agent improving the interface bonding and the cross-linking agent enhancing the internal structural strength allows the solid surface material to maintain a stable shape in a hot water environment, and the pigments dispersed inside are confined to an interwoven and stable three-dimensional space, which can effectively resist the erosion of hot water and prevent the precipitation of internal pigments. In addition, the addition of the curing agent promotes the curing reaction of the resin, further consolidates the formation of the cross-linking network, and ensures the stability and durability of the surface material in long-term use.

[0008] Preferably, the polyacrylate resin is polymerized from one or more of methyl acrylate, methyl methacrylate, butyl acrylate, n-butyl methacrylate, hexyl acrylate, octyl acrylate and derivatives thereof.

[0009] Preferably, the coupling agent is one or more of a silane coupling agent and a titanate coupling agent, wherein the silane coupling agent is such as γ-aminopropyltriethoxysilane, γ-glycidyloxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, octyltriethoxysilane, tetrabutyl titanate, etc.

[0010] Preferably, the crosslinking agent is a difunctional or trifunctional acrylate and its derivatives.

[0011] Preferably, the curing agent is one or more of methyl ethyl ketone peroxide, benzoyl peroxide, tert-butyl permaleate, and tert-butyl peroxy-2-ethylhexanoate.

[0012] Preferably, 0.1-2.6 parts of defoaming agent and 0.3-4 parts of antioxidant are also included.

[0013] Preferably, the defoaming agent is one or more of a non-silicon defoaming agent, a silicone defoaming agent, a polyether defoaming agent, and a polyether-modified silicone defoaming agent.

[0014] Preferably, water is also included, and the weight percentage of water is as follows: 水 =(0.8-2.0)×number of copies 偶联剂 ×(18*n 偶联剂的水解基团数 ) / m 偶联剂 , where the number of copies 水 is the weight percentage of water in the component, 偶联剂 is the weight fraction of coupling agent in the component, n 偶联剂的水解基团数 is the number of hydrolyzed groups of the coupling agent molecule, m 偶联剂 is the molecular weight of the coupling agent.

[0015] The inventor unexpectedly discovered during the actual experiment that adding a specific proportion of water can further improve the hot water resistance of the solid surface material. The reason is that during the curing process of the system, water reacts with the siloxane in the coupling agent to hydrolyze the coupling agent. After hydrolysis, the hydroxyl groups on the surface of the coupling agent produce hydrogen bonds with the hydroxyl groups on the surface of aluminum hydroxide, making the aluminum hydroxide, coupling agent and resin more tightly combined and having better hot water resistance.

[0016] Preferably, the water is deionized water.

[0017] A method for preparing a solid surface material with excellent hot water resistance comprises the following steps:

[0018] Step 1: Weigh the raw materials according to weight, fully mix the polyacrylate resin, pigment and aluminum hydroxide, and stir evenly to obtain a mixture;

[0019] Step 2: Mix the mixture of step 1 with a coupling agent, a cross-linking agent, a defoaming agent, an antioxidant, and a curing agent, and evacuate the mixture to obtain a casting material;

[0020] Step 3: Pour the casting material of step 2 into the mold, heat it up to solidify it, and demould it after cooling to obtain a solid surface material with excellent hot water resistance.

[0021] Preferably, in step 1, the temperature is 30-40° C. and the stirring time is 0.5-2 h.

[0022] Preferably, in step 2, the vacuum degree is -0.08-0.1 MPa and the time is 0.5-1 h.

[0023] Preferably, in step 3, the curing temperature is 80-100° C. and the curing time is 1-3 hours.

[0024] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention significantly improves the stability of the solid surface material through the synergistic effect of the coupling agent and the cross-linking agent, consolidates the cross-linking network inside the material, prevents the pigment from being precipitated by hot water, and ensures the stability and durability of the surface material in long-term use. DETAILED DESCRIPTION

[0025] In order to more clearly and completely describe the technical solution of the present invention, the present invention is further described in detail through specific embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention, and are not used to limit the present invention. Various changes can be made within the scope of the rights of the present invention.

[0026] Some of the reagents selected in the embodiments and comparative examples of the present invention are described as follows:

[0027] Polyacrylate resin was purchased from Foshan Sanshui Xiejia Chemical Co., Ltd.

[0028] Aluminum hydroxide was purchased from Changyuan Mingyu Aluminum Co., Ltd.

[0029] The coupling agent was purchased from Shandong Huachen New Materials Co., Ltd.

[0030] The cross-linking agent was purchased from Guangzhou Sanwang Chemical Co., Ltd.

[0031] The curing agent was purchased from Wuhan Jiyesheng Chemical Co., Ltd.

[0032] In order to better observe the changes in color depth, carbon black was selected as the pigment, purchased from Cabot Carbon Black REGAL 330R.

[0033] Examples 1 to 8

[0034] Embodiment 1:

[0035] The method for preparing a solid surface material with excellent hot water resistance according to the present invention comprises the following steps:

[0036] Step 1: Weigh 35 parts of polymethyl acrylate resin, 4 parts of pigment carbon black, and 65 parts of aluminum hydroxide, and stir them at 32±1°C for 2 hours to make them uniform.

[0037] Step 2: Based on the prepolymer obtained in step 1, add 0.8 parts of cross-linking agent ethylene glycol dimethacrylate, 0.5 parts of coupling agent γ-methacryloxypropyl trimethoxysilane, 0.2 parts of defoaming agent polydimethylsiloxane, 0.3 parts of antioxidant TH-1790, and 0.5 parts of curing agent methyl ethyl ketone peroxide, and stir at 32±1°C for 1 hour to make it evenly stirred. After stirring, evacuate at a vacuum degree of 0.1MPa for 0.5 hours.

[0038] Step 3: Pour the castable in step 2 into the mold, heat it to 90°C for curing, the curing time is 3 hours, and demould it after cooling to obtain a solid surface material with excellent hot water resistance.

[0039] Embodiment 2:

[0040] The difference between Example 2 and Example 1 is that 0.5 parts of cross-linking agent ethylene glycol dimethacrylate and 0.8 parts of coupling agent γ-methacryloxypropyltrimethoxysilane are added in step 2, and the rest is the same as Example 1.

[0041] Embodiment 3:

[0042] The difference between Example 3 and Example 1 is that 0.3 parts of cross-linking agent ethylene glycol dimethacrylate and 1 part of coupling agent γ-methacryloxypropyltrimethoxysilane are added in step 2, and the rest is the same as Example 1.

[0043] Embodiment 4:

[0044] The difference between Example 4 and Example 1 is that step 2 is:

[0045] On the basis of the prepolymer obtained in step 1 of Example 1, 0.5 parts of cross-linking agent triallyl isocyanurate, 1.4 parts of coupling agent tetrabutyl titanate, 0.2 parts of defoaming agent polydimethylsiloxane, 0.4 parts of antioxidant TH1135, and 0.4 parts of curing agent tert-butyl peroxide maleate were added, and stirred at 32±1°C for 1 hour to make it uniform. After stirring, evacuate at a vacuum degree of 0.1 MPa for 0.5 hours.

[0046] Step 2: Pour the castable in step 1 into the mold, heat it to 100°C for curing, the curing time is 2 hours, and demould it after cooling to obtain a solid surface material with excellent hot water resistance.

[0047] Embodiment 5:

[0048] The difference between Example 5 and Example 4 is that 0.9 parts of cross-linking agent triallyl isocyanurate and 1.0 parts of coupling agent tetrabutyl titanate are added in step 1, and the rest is the same as Example 4.

[0049] Embodiment 6:

[0050] The difference between Example 6 and Example 4 is that 1.3 parts of cross-linking agent triallyl isocyanurate and 0.6 parts of coupling agent tetrabutyl titanate are added in step 1, and the rest is the same as Example 4.

[0051] Embodiment 7:

[0052] The difference between Example 7 and Example 1 is that after adding 0.5 parts of coupling agent in step 2, 0.11 parts of deionized water are added, and the rest is the same as Example 1.

[0053] Embodiment 8:

[0054] The difference between Example 8 and Example 7 is that 0.20 parts of deionized water is added, and the other aspects are the same as Example 7.

[0055] Comparative Examples 1-2

[0056] Comparative Example 1:

[0057] To facilitate the performance comparison test, the difference between Comparative Example 1 and Example 1 is that 1.3 parts of cross-linking agent ethylene glycol dimethacrylate and 0 parts of coupling agent γ-methacryloxypropyltrimethoxysilane are added in step 2, and the rest is the same as Example 1.

[0058] Comparative Example 2:

[0059] To facilitate the performance comparison test, the difference between Comparative Example 2 and Example 4 is that 1.9 parts of the cross-linking agent triallyl isocyanurate and 0 parts of the coupling agent tetrabutyl titanate are added in step 1, and the rest is consistent with Example 4.

[0060] Performance Test:

[0061] Hot water resistance test: Cut the prepared solid surface material into 50mm×50mm samples, boil them in a water bath at 90℃ for 2h, and use a colorimeter to measure the color difference of the solid surface material before and after boiling. The smaller the color difference change value, the better the hot water resistance of the solid surface material.

[0062] Bending strength test: Referring to GB / T2567-2008, a sample with a specification of 240mm×200mm×12mm was prepared, and the bending strength of the prepared solid surface material was tested using a universal testing machine.

[0063] Impact strength test: referring to GB / T2567-2008, a sample with a specification of 130 mm × 13 mm × 12 mm was prepared, and the bending strength of the prepared solid surface material was tested using a simply supported beam pendulum impact tester.

[0064] The performance test results are shown in Table 1.

[0065] Table 1

[0066]

[0067] From the comparison of the examples and comparative data in the above table, it can be seen that in the component system of the technical solution of the present invention, the addition of a coupling agent is conducive to a significant improvement in the overall hot water resistance. The color value of the solid surface material prepared by the embodiment of the present invention before the test was approximately L=33.06, a=1.42, b=1.37. Since the number of pigments added to each formula is the same, the color difference is not significant. After analysis, in the test results of the above embodiments, the hot water resistance is ≤1.98ΔE, the bending strength is ≥64MPa, and the impact strength is ≥4.3kJ / m 2 In the component system of the technical solution of the present invention, the addition of coupling agent is conducive to significantly improving the overall hot water resistance. However, the ΔE of similar products (with similar color values) currently available on the market is in the range of about 1.8-5.0.

[0068] From the comparison of Examples 1-3, it can be seen that as the proportion of coupling agent used increases, the bonding strength between the resin and the powder is better, and the hot water resistance of the solid surface material is better. The inventor believes that the higher the coupling agent content, the more coupling agent molecules per unit area, the tighter the bonding between the resin and the powder, which leads to better hot water resistance of the solid surface material and correspondingly improved mechanical properties.

[0069] By comparison of Examples 4-6, it can be seen that by replacing different types of cross-linking agents, another solid surface material with better bending strength and slightly reduced hot water resistance can be prepared to meet the use requirements of different customers. For example, the bathtub focuses more on hot water resistance, and it is necessary to ensure that the fading is not serious during the circulation of hot water. The washbasin focuses more on the mechanical properties of bending strength, and the requirements for hot water resistance are relatively low. The cross-linking agent used in Examples 1-3 with good hot water resistance is a difunctional cross-linking agent (ethylene glycol dimethacrylate), while the cross-linking agent used in Examples 4-6 is a trifunctional cross-linking agent (triallyl isocyanurate). The price of the difunctional cross-linking agent is about 1 times more expensive than that of the trifunctional cross-linking agent. Therefore, through the above-mentioned cross-linking agent selection, the production cost of the panel can be flexibly controlled while meeting the hot water resistance of the customer's product.

[0070] From the comparison between Examples 1 and 7-8, it can be seen that by adding a certain proportion of water, the hot water resistance of the product can be further improved to a level of 0.8, which can meet the hot water resistance requirements of high-end surface materials. After the coupling agent is hydrolyzed, hydroxyl groups are grafted onto the surface of the coupling agent. The hydroxyl groups interact with the hydroxyl groups on the surface of aluminum hydroxide to form hydrogen bonds, which are more tightly bound to the powder, so its mechanical properties are improved. In addition, the mechanical strength is also improved. In Example 7, the coupling agent is γ-methacryloxypropyltrimethoxysilane. The purpose of adding 0.11 parts of water is that 0.11 parts of water are required to completely hydrolyze 0.5 parts of the coupling agent. The calculation method is as follows: 1 coupling agent molecule has 3 hydrolysis groups, one water molecule and one hydrolysis group. Combining the molecular weights of the two, the molecular weight of the coupling agent γ-methacryloxypropyltrimethoxysilane is 248, and the molecular weight of water is 18. According to the calculation formula, 水 =Number of copies 偶联剂 ×(18*n 偶联剂的水解基团数 ) / m 偶联剂 , where the number of copies 水 is the weight percentage of water in the component, 偶联剂 is the weight fraction of the coupling agent in the component, n 偶联剂的水解基团数 is the number of hydrolyzed groups of the coupling agent molecule, m 偶联剂 is the molecular weight of the coupling agent, and the weight of water required for complete hydrolysis of the coupling agent is 0.5*(18*3) / 248=0.1088≈0.11 parts. According to a large number of experiments by the inventors, the coupling agent with hydrolyzable groups can basically further improve the hot water resistance and mechanical properties of the panel products after adding a certain proportion of water. However, the proportion of water added should not be excessive, otherwise the overall viscosity will decrease, and the performance will decrease. After research and experiments, the inventors found that the amount of water added is (0.8-2.0) parts. 偶联剂 ×(18*n 偶联剂的水解基团数 ) / m 偶联剂 It can better meet the use requirements. While ensuring high hot water resistance, it does not require additional coupling agent usage, thus reducing the cost of material production.

[0071] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A solid surface material with excellent hot water resistance, characterized in that: The invention comprises the following components in parts by weight: 32-40 parts of polyacrylate resin; 54-68 parts of aluminum hydroxide; 0.3-5.0 parts of coupling agent; 0.1-4 parts of cross-linking agent; 0.2-3.0 parts of curing agent; and 0.3-6 parts of pigment.

2. The solid surface material according to claim 1, characterized in that: The polyacrylate resin is polymerized from one or more of methyl acrylate, methyl methacrylate, butyl acrylate, n-butyl methacrylate, hexyl acrylate, octyl acrylate and derivatives thereof.

3. The solid surface material according to claim 1, characterized in that: The coupling agent is one or more of a silane coupling agent and a titanate coupling agent.

4. The solid surface material according to claim 1, characterized in that: The crosslinking agent is difunctional or trifunctional acrylate and its derivatives.

5. The solid surface material according to claim 1, characterized in that: The curing agent is one or more of methyl ethyl ketone peroxide, benzoyl peroxide, tert-butyl permaleate, and tert-butyl peroxy-2-ethylhexanoate.

6. The solid surface material according to claim 1, characterized in that: Also included are 0.1-2.6 parts of defoaming agent and 0.3-4 parts of antioxidant.

7. The solid surface material according to claim 6, characterized in that: The defoaming agent is one or more of a non-silicon defoaming agent, an organosilicon defoaming agent, a polyether defoaming agent, and a polyether-modified organosilicon defoaming agent.

8. The polypropylene composition according to claim 6, characterized in that: The antioxidant is one or more of 1010, 1076, TH-1790, TH1135 and THP24.

9. The solid surface material according to claim 1, characterized in that: It also includes water, and the weight percentage of water is as follows: 水 =(0.8-2.0)×number of copies 偶联剂 ×(18*n 偶联剂的水解基团数 ) / m 偶联剂 , where the number of copies 水 is the weight percentage of water in the component, 偶联剂 is the weight fraction of coupling agent in the component, n 偶联剂的水解基团数 is the number of hydrolyzed groups of the coupling agent molecule, m 偶联剂 is the molecular weight of the coupling agent.

10. A method for preparing a solid surface material with excellent hot water resistance, characterized in that: The steps include: Step 1: Weigh the raw materials according to weight, fully mix the polyacrylate resin, pigment and aluminum hydroxide, and stir evenly to obtain a mixture; Step 2: mixing the mixture of step 1 with a coupling agent, a cross-linking agent, a defoaming agent, an antioxidant, and a curing agent, and evacuating the mixture to obtain a casting material; Step 3: Pour the casting material of step 2 into a mold, heat it up to solidify it, and demould it after cooling to obtain a solid surface material with excellent hot water resistance.